ANALISIS PENGELOLAAN KEUANGAN PROGRAM PEMBERDAYAAN EKONOMI KELUARGA BKKBN PORVINSI KALIMANTAN SELATAN - Mei Nanda Maulida; Imawati Yousida; Tina Lestari (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the Financial Management that has been applied to the Family Economic Empowerment Program of the National Population and Family Planning Agency (BKKBN) of South Kalimantan Province so far. The secondary data source of this research is data from the BKKBN of South Kalimantan Province. While the primary data of this study were obtained from direct observation by distributing questionnaires and interviews, as well as documentation to UPPKA who are members of the family economic empowerment program. The method of analysis in this research is to use Field Research data processing and analysis. The data processing process was analyzed qualitatively through several stages from the data that had been collected, compiled beforehand based on data obtained from the BKKBN of South Kalimantan Province, and from the results of questionnaires, interviews, and documentation. Based on the analysis results show that financial management in the family economic empowerment program has not been implemented optimally. There are still elements whose application is low because the UPPKA who are members of this family economic empowerment program experience obstacles in their implementation. The item that is most widely applied is the planning element, while the lowest is the reporting element.